Perception of the educational environment by dental students undergoing a curricular transition in a Peruvian sample - Salcedo Moncada, Doris (2014)
The objective of this study was to compare the perception of the educational climate of San Marcos University dental students, in a period of approximately six months after implementation of the new undergraduate curriculum project, with the perception of students still found in the previous or traditional curriculum, taking into consideration the semester or year of study and gender. Methodology: it were surveyed 169 students representing 40% of all students enrolled, 129 of them belong to the new curriculum with mixed regime studies: semester in most asignatures and anual in integrated clinical asignatures; 40 belong to the previous regime curriculum with annual study for all asignatures. 53.3% of students were male and 46.7% female equitably distributed by semester or year of study and randomly chosen. The spanish version of Questionnaire Dundee Ready Education Environment Measure DREEM that evaluates the educational climate in schools of health professions, was used. Results and conclusions: a more positive than negative educational climate was found, with average score in the total sample of 136.83 ± 19.00. No significant differences between the perception of the student’s educational climate of the new curriculum and the traditional, nor between years of education, or gender were found.El objetivo de ésta investigación fue comparar la percepción del clima educativo de los estudiantes de odontología de la Universidad Nacional Mayor de San Marcos, en un período aproximado de seis meses posterior a la implementación del nuevo proyecto curricular en pregrado, con la percepción de los estudiantes que todavía se encuentran en el plan curricular anterior o tradicional, tomando en consideración el semestre o año de estudio y el género. Metodología: se encuestaron 169 estudiantes que representan el 40 % del total de estudiantes matriculados, de los cuales 129 pertenecen al nuevo currículo con régimen de estudios mixto: semestral en la mayoría de asignaturas y anual en las asignaturas clínicas integradas; y 40 que pertenecen al currículo anterior con régimen de estudio anual para todas las asignaturas. El 53.3 % de estudiantes eran del sexo masculino y el 46.7% del sexo femenino distribuidos equitativamente según semestre o año de estudio y seleccionados en forma aleatoria. Se utilizó el cuestionario Dundee Ready Education Environment Measure DREEM que evalúa el clima educacional en las escuelas de profesiones de salud versión en español. Resultados y conclusiones: se encontró un clima educativo más positivo que negativo con puntaje promedio en la muestra total de 136.83 ± 19.00. No se encontraron diferencias significativas entre la percepción del clima educacional del estudiante del nuevo plan curricular y el tradicional, tampoco entre años de estudios, ni género.